Availability of clean water and Acute Respiratory Infection (ARI) cases among fishermen - Muslim Hadinata; Dharina Baharuddin; Putri Nahrisah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Acute Respiratory Infection (ARI) is one of the diseases with high morbidity, especially in coastal communities. Fishermen face a high risk of ARI due to the work environment, poor sanitation, and limited access to clean water. Purpose: To examining the relationship between the availability of clean water and the incidence of ARI in fishermen in Aceh Jaya District. Method: An analytical observational study with a cross-sectional design was conducted on 200 fishermen in two villages using a total sampling technique. Data were analyzed using the chi-square test and logistic regression using STATA. Results: There is a significant relationship between the availability of clean water (p=0.000), water source (p=0.000), water condition (p=0.000), ease of access (p=0.000), and the availability of clean water within a certain period of time (p=0.000) with the incidence of ARI. Conclusion: Access to clean water plays an important role in preventing ARI. Efforts to increase the availability of clean water and sanitation are needed to reduce the incidence of ARI in fishing communities. Suggestion: To examine other factors contributing to the incidence of ARI, such as air quality.